2014
DOI: 10.1186/1471-2474-15-188
|View full text |Cite
|
Sign up to set email alerts
|

The development of a comprehensive multidisciplinary care pathway for patients with a hip fracture: design and results of a clinical trial

Abstract: BackgroundHip fractures frequently occur in older persons and severely decrease life expectancy and independence. Several care pathways have been developed to lower the risk of negative outcomes but most pathways are limited to only one aspect of care. The aim of this study was therefore to develop a comprehensive care pathway for older persons with a hip fracture and to conduct a preliminary analysis of its effect.MethodsA comprehensive multidisciplinary care pathway for patients aged 60 years or older with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 25 publications
4
41
2
1
Order By: Relevance
“…One was a subgroup analysis of an included trial, 20 two did not record delirium as an outcome measure, 21,22 and six were not RCTs. [23][24][25][26][27][28]…”
Section: Excluded Studiesmentioning
confidence: 99%
“…One was a subgroup analysis of an included trial, 20 two did not record delirium as an outcome measure, 21,22 and six were not RCTs. [23][24][25][26][27][28]…”
Section: Excluded Studiesmentioning
confidence: 99%
“…A hip fracture is a devastating event for a patient. Many studies (Biber et al., ; Burgers et al., ; Flikweert et al., ; Gupta, ; Lau et al., ; Leigheb et al., ; Lynch et al., ; Neuman et al., ; Zeltzer et al., ) have confirmed that using a hip fracture clinical pathway and an ortho‐geriatrician‐led program can improve clinical outcomes for patients with minimal trauma hip fracture. The major findings from this study show that the implementation of the role of the ONP to co‐ordinate care for patients with hip fracture decreased the acute hospital LOS.…”
Section: Discussionmentioning
confidence: 98%
“…A hip fracture is a devastating event for a patient. Many studies (Biber et al, 2013;Burgers et al, 2014;Flikweert et al, 2014;Gupta, 2014;Lau et al, 2013;Leigheb et al, 2012;Lynch et al, 2015;Neuman et al, 2009;Zeltzer et al, 2014) Similar to the Nurse Practitioner role, the ONP in this study coordinated the delivery of patient care with the multidisciplinary team that was in alignment with evidenced-based practice; the role provided expert guidance and consultation; clinical and professional leadership; daily patient rounds and chart reviews; presented diagnostic treatment options to patients and families; organized referrals as applicable and prepared the patient and multidisciplinary team for discharge planning and follow-up (Kutzleb et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13][14] Baseline measurement A retrospective baseline audit was conducted on two months of hip fracture admissions from 2013. Patients were identified from NHFD records, and data gathered from their notes.…”
Section: Introductionmentioning
confidence: 99%